Evaluation of Povidone-Iodine in Pleurodesis of Malignant Pleural Effusion (Journal of Academic Research, 2023)
Background: Malignant pleural effusion (MPE) is a condition that malignant cells are presented in the pleural fluid. 10% povidone-iodine in pleurodesis is one of (MPE) treatment options. This study aims  to evaluate the safety, efficacy and the success rate of 10% povidone-iodine in pleurodesis procedure through thoracostomy by conducting; the assessment of  radiological  and clinical outcome after using of povidone –iodine as a chemical pleurodesis agent.Randomized clinical trial, was carried out on 18 cases  at Thoracic Surgery Department, Abuslem Trauma Center, Tripoli 2020 - 2021, all patients who underwent pleural drainge and received bedside mixture of 20 ml of 10% topical solution of povidone-iodine and 80 ml of normal saline, was Instilled into the pleural cavity through pleural catheter and then, the tube was clamped for 1 hour.In the absence of excessive fluid drainage (> 250 mL/ day) and no fluid collection in chest x ray, the pleural catheter removed within 24-48 hours of sclerosant administration pleurodesis with 10% povidone-iodine.     After pleurodesis, all patients were assessed via chest X-ray (CXR) after procedure, and at one month.Data collected throughout history, basic clinical examination, laboratory investigations and outcome measures coded, entered and analyzed using Microsoft Excel software.Results: revealed that early response was 72.2% complete, partial in 16.6%, and failure 11.1%, major complication was nausea.We concluded that povidone-iodine is a safe and effective agent with minor side effects in pleurodesis and treatment of MPE and proposed povidone-iodine as a proper, accessible, and low-cost alternative sclerosing agent.